Literatur Review: Efektivitas Layanan Konseling Pendekatan CBT Untuk Mereduksi Perilaku Prokrastinasi Akademik Siswa - Zahara, Willya; Fitriani, Wahidah (Jurnal Konseling Komprehensif: Kajian Teori dan Praktik Bimbingan dan Konseling, 2024)
This study aims to explore the effectiveness of Cognitive Behavioral Therapy (CBT) based counseling services in reducing academic procrastination behavior among students. Procrastination is a common problem that interferes with student achievement and mental health, often causing stress and anxiety. Although there has been much research on procrastination, there is still a lack of studies evaluating the application of CBT techniques in an educational context. This study used the literature review method to analyze various studies evaluating the application of CBT techniques in educational contexts. The results of the analysis show that the techniques significantly help students identify and overcome negative thoughts that result in procrastination in completing tasks. Students who participated in counseling sessions showed increased motivation to learn and decreased procrastination behavior. This study highlights the importance of implementing CBT-based counseling strategies in education, which can contribute to the development of more effective counseling programs. Recommendations for further research include exploring the long-term effects of CBT interventions on various student populations, as well as evaluating different CBT techniques. The results of this study are expected to serve as a reference for educators and counseling practitioners in addressing academic procrastination in educational settings.